Dynamical analysis of carbon concentration model due to the interaction with biomass production based on predator-prey - Hafizan, Juahir; Mustafa, Mamat; Budiono, R; Sukono, .; Putra, A.S.; Bon, A.T. (2019)
The high energy demands and the development of technology produce transcendent concentration of atmospheric Carbon dioxide gas emission. Many studies have been conducted to develop a model of the carbon dioxide cycle to understand its characters. Here, we proposed the model of the interaction between Carbon consumption due to the biomass production. The model is currently developed to characterize the dynamical behaviour of the climate vector of the gas to predict its stability. We simulated the Rungge-Kutta method to analyze the bifurcation and define the Jacobian matrix to see the eigen value. The result gave the idea that the gas concentration can be controlled by manipulating its uncertain parameters and could be a provisional prediction for several years ahead.